ASSISTANCE FOR THE DRAFT OF WORKING CONTRACT AGREEMENT FOR EMPLOYEES AT CV TRANS MANDIRI SUKSES - Nur Hadiyati; Rinto Sibarani (ConCEPt - Conference on Community Engagement Project, 2022)
The implementation of community service carried out by the author this time is located at CV Trans Mandiri Sukses. Where CV Trans Mandiri Sukses is a sewing clothing industry business that was founded on December 22, 2018, and until now it has had 4 employees including the owner, and based on observations and interviews with the owner of the CV it was found the fact that the business was founded until now there is no legal certainty regarding written work agreements made between the owner and his employees because the worker acceptance system is only limited to verbal delivery. So that there is no clear certainty between the workers and the business owners regarding the rights and obligations of each party, for this reason the author takes the title, namely Assistance in the Preparation of a Draft Employment Contract Agreement for Employees at CV Trans Mandiri Sukses. It is hoped that this service can help partners related to drafting work agreements for employees at CV Trans Mandiri Sukses which can be used in the future. During the service carried out, the author uses an implementation method which is divided into 4 stages, namely the preparation stage by conducting surveys and interviews, the implementation stage by engaging in service, the assessment stage by concluding the results of the question and answer session with partners and supervisors and the reporting stage by making a service report. community based on data obtained during service which consists of articles, draft work agreements and service reports which are then able to answer problems for partners so far